1998
DOI: 10.1016/s0014-5793(98)01362-3
|View full text |Cite
|
Sign up to set email alerts
|

Endomorphins fully activate a cloned human mu opioid receptor

Abstract: Endomorphins were recently identified as endogenous ligands with high selectivity for mu opioid receptors. We have characterized the ability of endomorphins to bind to and functionally activate the cloned human mu opioid receptor. Both endomorphin-1 and endomorphin-2 exhibited binding selectivity for the mu opioid receptor over the delta and kappa opioid receptors. Both agonists inhibited forskolin-stimulated increase of cAMP in a dose-dependent fashion. When the mu opioid receptor was coexpressed in Xenopus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…5B). This is in agreement with evidence that endomorphin-1 is a partial agonist at the rat -opioid receptor (Hosohata et al, 1998;Sim et al, 1998) (but see Gong et al, 1998). No apparent desensitization of the receptor was observed after 3 hr of treatment of the receptor with 1 M endomorphin-1 (Table 2).…”
Section: Endomorphin-1 Selectively Binds To the Clonedopioid Receptorsupporting
confidence: 90%
“…5B). This is in agreement with evidence that endomorphin-1 is a partial agonist at the rat -opioid receptor (Hosohata et al, 1998;Sim et al, 1998) (but see Gong et al, 1998). No apparent desensitization of the receptor was observed after 3 hr of treatment of the receptor with 1 M endomorphin-1 (Table 2).…”
Section: Endomorphin-1 Selectively Binds To the Clonedopioid Receptorsupporting
confidence: 90%
“…The first saturable transport system across the BBB to be shown for a peptide was for Tyr-MIF-1 (Tyr-Pro-Leu-Gly-NH 2 ) (Banks and Kastin 1984). Endomorphin-1 (EM-1) and endomorphin-2 (EM-2), are two endogenous peptides selectively activating mu-opiate receptors (Zadina et al 1997;Goldberg et al 1998;Gong et al 1998;Hosohata et al 1998). The endormorphins are structurally similar to Tyr-MIF-1.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that Endos hyperpolarize membrane potential [26], activate inwardly rectified K+ currents [6] and block voltage-dependent Ca 2+ current [4]. However, it is not clear whether Endos reduce synaptic transmission by pre-or postsynaptic mechanism.…”
Section: Endomorphin Inhibition Of Transmitter Release In the Sgmentioning
confidence: 99%